The only thing - Harte, Marie (Harte, Marie. Donnigans, 2018)
What do you do when a "fake" relationship is so much better than the real thing? Hope Donnigan is finally getting her life together. She's working a job she likes, has some amazing friends, and is steering clear of Mr. Wrong. Now if only she could get her mother to understand that. Maybe a hot tattoo artist from the other side town is just the ticket to teach her mom a lesson. J.T. Webster fell for Hope months ago at his sister's wedding. So when she propositions him to be her fake boyfriend to get her mother off her back, he's all in. The only problem is J.T. had no idea their pretend relationship would be better than anything real he's ever had...